Regulating sex for sale : Prostitution Policy Reform in the UK - Phoenix, Jo (Book collections on Project MUSE., 2009)
Regulating sex for sale' provides a detailed analysis and critical reflection on the processes, assumptions and contradictions shaping the UK's emerging prostitution policy. It examines the total package of reforms and proposals that have been introduced in this area since May 2000.